Clinically significant findings in a decade‐long retrospective study of prenatal chromosomal microarray testing - Joie O. Olayiwola; Mohammad Marhabaie; Daniel Koboldt; Theodora Matthews; Amy Siemon; Danielle Mouhlas; Taylor Porter; George Kyle; Cortlandt Myers; Hui Mei; Ying‐Chen Claire Hou; Melanie Babcock; et al. (Molecular Genetics & Genomic Medicine, 2024)
Abstract Background Chromosomal microarray (CMA) is commonly utilized in the obstetrics setting. CMA is recommended when one or more fetal structural abnormalities is identified. CMA is also commonly used to determine genetic etiologies for miscarriages, fetal demise, and confirming positive prenatal cell‐free DNA screening results. Methods In this study, we retrospectively examined 523 prenatal and 319 products‐of‐conception (POC) CMA cases tested at Nationwide Children's Hospital from 2011 to 2020. We reviewed the referral indications, the diagnostic yield, and the reported copy number variants (CNV) findings. Results. In our cohort, the diagnostic yield of clinically significant CNV findings for prenatal testing was 7.8% (n = 41/523) compared to POC testing (16.3%, n = 52/319). Abnormal ultrasound findings were the most common indication present in 81% of prenatal samples. Intrauterine fetal demise was the common indication identified in POC samples. The most common pathogenic finding observed in all samples was isolated trisomy 21, detected in seven samples. Conclusion Our CMA study supports the clinical utility of prenatal CMA for clinical management and identifying genetic etiology in POC arrays. In addition, it provides insight to the spectrum of prenatal and POC CMA results as detected in an academic hospital clinical laboratory setting that serves as a reference laboratory.